Engaging Sexual and Gender Minority College Students to Understand Mechanisms of Alcohol-Related Harms Through Complex Systems Science - Michelle Dougherty; Travis R. Moore; Christina Mair; Jaime E. Sidani; Kar-Hai Chu; Robert W.S. Coulter (Journal of Participatory Research Methods)
Sexual and gender minority (SGM) college students experience inequities in alcohol-related harms. Group model building (GMB) is a participatory systems science method useful for identifying complex drivers and intervention points; however, its feasibility for engaging SGM college students to understand mechanisms underlying alcohol-related harms is unclear.